Pengaruh Religiusitas dan Pengetahuan tentang Produk Perbankan Syariah terhadap Keputusan Masyarakat Kota Palembang Menabung di Bank Syariah Indonesia - Aisyah Zahara; Rinol Sumantri; Oki Sania Riski (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to test and determine the influence of religiosity and knowledge about sharia banking products on the decision of the people of Palembang to save at Indonesian sharia banks. Research Method This thesis is a type of quantitative research. This research uses one independent variable and one dependent variable. The independent variables in this research are religiosity and product knowledge, while the dependent variable in this research is people's decision to save in Islamic banks. The data collection technique in this research was in the form of a questionnaire distributed to 100 respondents and the data was analyzed using the PLS (Partial Least Square) analysis technique. In analyzing the data, researchers used data analysis with several steps, namely validity test, reliability test, outer model test, inner model test and hypothesis test. The results of the hypothesis test carried out show the significance value of the influence of religiosity (X1) and knowledge about sharia banking products (X2) on the decision of the people of Palembang to save at Indonesian sharia banks (Y). The results of the research show that the religiosity variable obtained a t-statistic value of 7,540 > 1.96 with a p-value of 0.000 < less than the significance level of 0.05, so it can be explained that religiosity has a positive effect on the decision of the people of Palembang city to save at Indonesian sharia banks and the variable knowledge about products Islamic banking obtained a t-statistic value of 4,091 > 1.96 with a p-value of 0.000 < less than the significance level of 0.05, so it can be explained that knowledge about sharia banking products has a positive effect on the decision of the people of Palembang city to save at Indonesian sharia banks. The conclusion of this research is that religiosity and knowledge of sharia banking products influence the decision of the people of Palembang to save at Indonesian sharia banks.